The history and usefulness of Bioversity International’s descriptor lists - Bioversity International (2011)
Effective sharing of information about genetic resources depends on everyone using the same “dictionary” – which is where the descriptor lists published by Bioversity International and its partners come in. In a 2006 survey 90% or more of respondents stated that descriptor lists published by Bioversity and its partners had contributed to the development of genebank databases, increased uniformity of documentation, increased their ability to work with partners, increased efficiency in collection management, and facilitated data exchange. The utility of Bioversity’s descriptors was rated higher than those from other sources, including UPOV and USDA-GRIN, scoring an average of 3.3 on a 4-point scale. The most common constraint to using Bioversity descriptor lists was the lack of descriptors for a particular species of interest – highlighting the need to develop additional descriptor lists.